2018
DOI: 10.5114/pg.2018.74228
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic efficacy of amoxicillin and rifaximin in patients with small intestinal bacterial overgrowth and Helicobacter pylori infection

Abstract: IntroductionSmall intestinal bacterial overgrowth (SIBO) may coexist with Helicobacter pylori infection, which can be the cause of chronic gastrointestinal complaints.AimEvaluation of the therapeutic efficacy of amoxicillin and rifaximin in the treatment of these diseases.Material and methodsThe lactulose hydrogen breath test (LHBT) and the urea breath test (13C-UBT) were performed in 116 patients. In 62 patients the coexistence of small intestinal bacterial overgrowth and H. pylori infection was observed. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 31 publications
1
17
0
3
Order By: Relevance
“…Patients with H. pylori are more likely to test positive for SIBO ( 32 ). Further, H. pylori eradication therapy can effectively relieve the clinical symptoms of patients with SIBO ( 33 ), which also suggests there is some correlation between H. pylori infection, and SIBO and IBS. Anti- H. pylori treatment may relieve the clinical symptoms of IBS by ameliorating SIBO.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with H. pylori are more likely to test positive for SIBO ( 32 ). Further, H. pylori eradication therapy can effectively relieve the clinical symptoms of patients with SIBO ( 33 ), which also suggests there is some correlation between H. pylori infection, and SIBO and IBS. Anti- H. pylori treatment may relieve the clinical symptoms of IBS by ameliorating SIBO.…”
Section: Discussionmentioning
confidence: 99%
“…SIBO is a common gastrointestinal dysbiosis that can be caused by the overuse of certain drugs such as proton pump inhibitors. The long-term reduction of gastric secretion creates favorable conditions for the colonization of various bacterial species in the upper gastrointestinal tract [146]. Moreover, it is also known that H. pylori infection can also alter the microbiota of the upper gastrointestinal tract, and active H. pylori infection has been found to be significantly associated with the presence of SIBO [146,147].…”
Section: Clinical Benefits Of Tyndallized Bacteria As Probiotics Imentioning
confidence: 99%
“…Some studies have corroborated that thyroid disorders are the causal factor in the relationship with gut microbes. Other studies have demonstrated that bacteria might act as the motivating factor, as thyroid function may be impaired in patients with small intestinal bacterial overgrowth (140,141). However, the causative role of Se deficiency, thyroid and gut microbiota has not been thoroughly ascertained yet and further clinical studies are highly recommended.…”
Section: Selenium Microbiota and Thyroid Dysfunctionsmentioning
confidence: 99%